Solid self-generating acid reservoir deep reconstruction agent, preparation method and application thereof

CN122959014APending Publication Date: 2026-10-23PETRO KING OILFIELD TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611096213.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-23
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0004]上述固体酸的现有技术仍存在以下不足:(1)部分固体酸是通过覆材直接包裹强酸(如盐酸),在包覆不完整或受外力破损时易造成早期释放,且腐蚀性风险依然存在;(2)酸前体(如三氟甲磺酸酯)虽安全,但水解速率受温度影响大,难以在储层远端维持有效酸浓度;(3)双敏感聚合物载体虽能响应pH和温度,但载酸量有限,且聚合物骨架本身不参与生酸,有效酸当量较低;(4)均未考虑对储层渗透率和酸蚀通道均匀性的优化,存在虫洞效应

Benefits of technology

本发明实施例提供的固体自生酸,其包括中间层有机酸、核心层的骨架酸以及核心层的强酸,中间层的有机酸作为最先释放的酸源,对裂缝壁面进行初步不均匀刻蚀,提供局部酸性微环境;聚乙醇酸、聚乳酸作为骨架缓释酸源,在储层高温和酸性条件下缓慢水解释放乙醇酸和乳酸;负载在介孔二氧化硅中的三氟甲磺酸,在骨架降解后暴露于水相,水解生成三氟甲磺酸(pKa≈-14),对弱酸无法到达的微孔隙和裂缝尖端进行深度酸化。三种酸源协同作用,实现有机弱酸的速效刻蚀,骨架酸源的长效缓释,以及强酸的超强渗透,可提高有效酸蚀缝长,酸液可渗透到储层深部,从而实现从裂缝壁面表层到微孔隙尖端全尺度酸化。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to the field of solid acid, specifically, it relates to a kind of solid autogenic acid reservoir deep reconstruction agent and its preparation method and application, including core layer, isolation layer, intermediate layer and cladding layer;The core layer includes the following raw materials according to mass percentage: polyglycolic acid 40-50%, polylactic acid 10-30%, trifluoromethanesulfonate 5-10%, ammonium fluoride 5-10%, hexadecyl trimethyl ammonium chloride 0.5-1%, mesoporous silica 3-5%, plasticizer 3-5%;The isolation layer is polylactic acid-glycolic acid copolymer;The intermediate layer includes the following raw materials according to mass percentage: organic acid 70-80%, adhesive 20-30%;The cladding layer is polyisobutylene.Multiple layer structure and multiple acid cooperation are used, acid source can penetrate into deep reservoir, effective acid etching seam length, and fracture conductivity is strong.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid acids, and more specifically, to a solid self-generating acid reservoir deep modification agent, its preparation method, and its application. Background Technology

[0002] As oil and gas exploration and development advances to deeper and ultra-deep formations, high-temperature and high-pressure carbonate reservoirs have become key targets for increasing reserves and production. These reservoirs have low matrix permeability and strong heterogeneity, necessitating acid fracturing to create long fractures and improve conductivity. However, conventional acids (such as hydrochloric acid and terrine acids) react extremely rapidly at high temperatures, limiting their effective range, and strong acids severely corrode wellbore tubing, posing high operational risks. Furthermore, the storage and transportation of liquid acids require special approvals and protective measures, resulting in high costs and safety hazards.

[0003] To address the aforementioned issues, various slow-release acid systems have been developed, including emulsified acids, gelling acids, and cross-linked acids, which reduce filtration loss through thickening. However, their slowing effect is not ideal, and the polymer residues can easily damage the reservoir. In recent years, solid acid and solid acid precursor technologies have attracted attention. For example, patent CN111502629A discloses a coated solid acid for deep acid fracturing of carbonate reservoirs, which encapsulates solid hydrochloric acid through a copolymer of water-soluble framework monomers and acid-resistant monomers, achieving temperature and pH-controlled release. Patent CN111154477A uses glycolic acid mixed with natural polymers, granulated, and coated, utilizing a polyglycolic acid membrane to control release. Patent CN102676150A proposes dispersing chlorocarboxylic acids in polylactic acid and coating them with a water-insoluble membrane to achieve slow acid release at high temperatures. Patent 202311156654.9 discloses a solid acid precursor with trifluoromethanesulfonate as the main agent, which hydrolyzes in water to generate organic acids, offering advantages such as safety, environmental friendliness, and good slow-release properties. Patent CN119552647A discloses a method for preparing a controllable release organic solid acid, which uses a pH and temperature-sensitive polymer carrier to load 2-acetoxypropionic acid and composite modified nano-silica to achieve multiple response release.

[0004] The existing technologies for solid acids still have the following shortcomings: (1) Some solid acids are directly wrapped with strong acids (such as hydrochloric acid) by coating materials. When the coating is incomplete or damaged by external force, it is easy to cause early release, and the risk of corrosion still exists; (2) Although acid precursors (such as trifluoromethanesulfonate) are safe, the hydrolysis rate is greatly affected by temperature, and it is difficult to maintain an effective acid concentration at the far end of the reservoir; (3) Although dual-sensitive polymer carriers can respond to pH and temperature, the acid carrying capacity is limited, and the polymer skeleton itself does not participate in acid generation, resulting in a low effective acid equivalent; (4) None of them have considered the optimization of reservoir permeability and acid corrosion channel uniformity, resulting in a wormhole effect. Summary of the Invention

[0005] The purpose of this invention is to provide a solid self-generating acid reservoir deep modification agent, which adopts a multi-layer structure and is combined with various acids. The acid source can penetrate deep into the reservoir, effectively creating long acid-etched fractures with strong fracture conductivity.

[0006] Another objective of this invention is to provide a method for preparing a solid self-generating acid reservoir deep modification agent, which involves coating layer by layer and is suitable for industrial production.

[0007] The third objective of this invention is to provide an application of a solid autogenous acid reservoir deep modification agent that remains chemically stable up to 180°C and is suitable for acid fracturing modification of ultra-deep (>6000m) and ultra-high temperature (>150°C) carbonate reservoirs.

[0008] The technical problem solved by this invention is achieved by the following technical solution.

[0009] On one hand, embodiments of the present invention provide a solid self-generating acid reservoir deep modification agent, comprising a core layer, an isolation layer, an intermediate layer, and a coating layer; The core layer comprises the following raw materials by weight percentage: Polyglycolic acid 40-50%, polylactic acid 10-30%, trifluoromethanesulfonate 5-10%, ammonium fluoride 5-10%, cetyltrimethylammonium chloride 0.5-1%, mesoporous silica 3-5%, plasticizer 3-5%; The isolation layer is a polylactic acid-glycolic acid copolymer; The intermediate layer comprises, by weight percentage, the following raw materials: 70-80% organic acid and 20-30% adhesive; The coating layer is polyisobutylene.

[0010] In some embodiments of the present invention, the organic acid is at least one selected from glycolic acid, lactic acid, citric acid, and chloroacetic acid; The adhesive is at least one of hydroxypropyl methylcellulose, polyvinylpyrrolidone, guar gum, and locust bean gum. The plasticizer is tributyl citrate or acetylated tributyl citrate.

[0011] In some embodiments of the present invention, the number-average molecular weight of the polyisobutylene is 1000-3000.

[0012] In some embodiments of the present invention, by mass fraction, the core layer is 50-70%, the isolation layer is 5-10%, the intermediate layer is 10-20%, and the covering layer is 8-10%.

[0013] On the other hand, embodiments of the present invention provide a method for preparing a solid self-generating acid reservoir deep modification agent, comprising the following steps: S1, using the impregnation method, trifluoromethanesulfonate is mixed with mesoporous silica, dried to obtain a composite, and then the composite is mixed evenly with the remaining raw materials of the core layer, extruded and granulated to obtain core layer particles. S2, the polylactic acid-glycolic acid copolymer is mixed with dichloromethane to prepare the first coating solution; the core layer particles are placed in a fluidized bed, the first coating solution is sprayed from the bottom, and dried to obtain the isolation layer particles; S3, mix the raw materials of the intermediate layer evenly, heat to a molten state, and prepare the second coating liquid; place the isolation layer particles in a fluidized bed, spray the second coating liquid from the bottom, dry and solidify, repeat the operation until the particle weight increases by 10-20%, and obtain the intermediate layer particles; S4. Polyisobutylene and cyclohexane are mixed to prepare a third coating solution; the intermediate layer particles are placed in a fluidized bed, and the third coating solution is atomized and sprayed onto the surface of the intermediate layer particles until the particle weight increases by 8-10%. The particles are then dried, annealed, and matured at room temperature for 24 hours to obtain the modifier.

[0014] In some embodiments of the present invention, step S1 includes drying mesoporous silica with an average pore size of 8-12 nm at 110-120°C for 4-5 hours for later use. Butyl trifluoromethanesulfonate and dichloromethane were mixed at a mass ratio of 1:1 to obtain a mixture. The mixture was added dropwise into dried mesoporous silica while stirring. It was allowed to evaporate at room temperature for 10-12 hours, and then dried under vacuum at 40°C for 4 hours to obtain the composite.

[0015] In some embodiments of the present invention, in step S2, the mass fraction of polylactic acid-glycolic acid copolymer in the first coating solution is 5-10%, the molar ratio of lactic acid to glycolic acid in the polylactic acid-glycolic acid copolymer is 85:15, the inlet air temperature is 50-60°C, and the drying time is 20-30 min.

[0016] In some embodiments of the present invention, in step S3, the inlet air temperature is 50-60°C and the spraying temperature of the second coating liquid is 90-100°C.

[0017] In some embodiments of the present invention, in step S4, the solid content of the third coating liquid is 5-10%, the inlet air temperature is 35-40°C, drying is performed at 40°C for 2-4 hours, and annealing is performed at 50°C for 4 hours.

[0018] Thirdly, embodiments of the present invention provide an application of a solid self-generating acid reservoir deep modification agent in deep carbonate reservoirs.

[0019] Compared with the prior art, the embodiments of the present invention have at least the following advantages or beneficial effects: The solid self-generating acid provided in this invention comprises an intermediate layer of organic acid, a core layer of skeletal acid, and a core layer of strong acid. The intermediate layer of organic acid serves as the first released acid source, performing preliminary non-uniform etching on the fracture wall and providing a localized acidic microenvironment. Polyglycolic acid and polylactic acid serve as the skeletal slow-release acid sources, slowly hydrolyzing and releasing glycolic acid and lactic acid under high reservoir temperature and acidic conditions. Trifluoromethanesulfonic acid, loaded in mesoporous silica, is exposed to the aqueous phase after skeletal degradation and hydrolyzes to generate trifluoromethanesulfonic acid (pKa≈-14), deeply acidifying micropores and fracture tips that weak acids cannot reach. The synergistic effect of the three acid sources achieves rapid etching of the organic weak acid, long-term slow release of the skeletal acid source, and super-strong penetration of the strong acid, increasing the effective acid-etched fracture length and allowing the acid to penetrate deep into the reservoir, thereby achieving full-scale acidification from the fracture wall surface to the micropore tip.

[0020] The solid acid provided by this invention adopts a multi-layer structure design. The outermost polyisobutylene is in a highly elastic state in the wellbore and near-wellbore zone (<100℃) with low water vapor permeability, which can ensure that the internal components are absolutely dry during the injection stage and avoid premature release of internal acid. After reaching the high temperature zone of the reservoir, it changes from a highly elastic state to a viscous flow state, and its mechanical strength decreases. It is then torn apart by the volume of the molten organic acid in the middle layer, releasing the internal acid source.

[0021] Polylactic acid-glycolic acid copolymer is used as the isolation layer. It is a dense hydrophobic film that can physically separate the organic acid in the middle layer from the polyglycolic acid in the core layer, effectively preventing the diffusion of organic acid molecules into the core and causing premature acid-catalyzed disintegration of polyglycolic acid. Detailed Implementation

[0022] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.

[0023] It should be noted that, unless otherwise specified, the embodiments and features described in the present invention can be combined with each other. The present invention will now be described in detail with reference to specific embodiments.

[0024] On one hand, embodiments of the present invention provide a solid self-generating acid reservoir deep modification agent, comprising a core layer, an isolation layer, an intermediate layer, and a coating layer; The core layer comprises the following raw materials by weight percentage: Polyglycolic acid 40-50%, polylactic acid 10-30%, trifluoromethanesulfonate 5-10%, ammonium fluoride 5-10%, cetyltrimethylammonium chloride 0.5-1%, mesoporous silica 3-5%, plasticizer 3-5%; The isolation layer is a polylactic acid-glycolic acid copolymer; The intermediate layer comprises, by weight percentage, the following raw materials: 70-80% organic acid and 20-30% adhesive; The coating layer is polyisobutylene, and the number-average molecular weight of polyisobutylene is 1000-3000.

[0025] The organic acid is at least one of glycolic acid, lactic acid, citric acid, and chloroacetic acid; The adhesive is at least one of hydroxypropyl methylcellulose, polyvinylpyrrolidone, guar gum, and locust bean gum. The plasticizer is tributyl citrate or acetylated tributyl citrate.

[0026] By mass fraction, the core layer is 50-70%, the isolation layer is 5-10%, the intermediate layer is 10-20%, and the covering layer is 8-10%.

[0027] The solid acid provided by this invention has the following functions for the components in its core layer.

[0028] Polyglycolic acid (PGA): It is a long-lasting acid-producing skeleton that slowly releases glycolic acid through the hydrolysis of ester bonds. The degradation time can take several days to several weeks, providing a continuous supply of acid.

[0029] Polylactic acid (PLA): It is another skeletal acid that can be blended and copolymerized with polyglycolic acid. When PLA degrades, it produces lactic acid, which works synergistically with glycolic acid to dissolve the core layer. In addition, PLA has good hydrophobicity, which can delay the penetration of water into the core layer.

[0030] Trifluoromethanesulfonate: As a strong acid precursor, it hydrolyzes into trifluoromethanesulfonic acid, providing high-strength acid etching ability in distal cracks; it complements lactic acid and glycolic acid, and can produce acid etching on both central and distal cracks.

[0031] Ammonium fluoride: provides protons to accelerate ester bond breaking; the HF produced by hydrolysis can synergistically dissolve siliceous minerals in sandstone reservoirs, achieving dual modification of carbonate and sandstone.

[0032] Hexadecyltrimethylammonium chloride: Prevents powder agglomeration during processing; acts as a lubricant and dispersant during melt extrusion; and also has certain antibacterial properties, preventing organic acids from becoming moldy during storage.

[0033] The organic acid in the intermediate layer is at least one of glycolic acid, lactic acid, citric acid, and chloroacetic acid; during use, the outer layer cracks and releases the acid first, causing initial uneven etching of the crack walls; the released H... + This creates a locally acidic microenvironment (pH drops to 3-4), providing acidic catalytic conditions for the subsequent hydrolysis of PGA and PLA in the core layer.

[0034] The coating layer is made of polyisobutylene, and the coating film formed by the coating process has low water vapor permeability, which can ensure that the contents are absolutely dry during storage at room temperature and well injection. At high temperature, the viscosity decreases, and it changes from a highly elastic state to a viscous flow state, and is torn apart and burst by the internal pressure of the core.

[0035] This solid acid is environmentally friendly; PGA, PLA, and PLGA are all biodegradable polyesters that ultimately degrade into water and CO2; the organic acid is a natural metabolic product; mesoporous SiO2 is a common mineral found in geological formations; and the complexing effect of ammonium fluoride effectively prevents calcium loss. 2+ Mg 2+ Fe 3+ Hydroxides or carbonates are formed in the near-wellbore zone to maintain the high permeability of the modified fractures.

[0036] A method for preparing a solid self-generating acid reservoir deep modification agent includes the following steps: S1, using the impregnation method, trifluoromethanesulfonate is mixed with mesoporous silica, dried to obtain a composite, and then the composite is mixed evenly with the remaining raw materials of the core layer, extruded and granulated to obtain core layer particles. S2, the polylactic acid-glycolic acid copolymer is mixed with dichloromethane to prepare the first coating solution; the core layer particles are placed in a fluidized bed, the first coating solution is sprayed from the bottom, and dried to obtain the isolation layer particles; S3, mix the raw materials of the intermediate layer evenly, heat to a molten state, and prepare the second coating liquid; place the isolation layer particles in a fluidized bed, spray the second coating liquid from the bottom, dry and solidify, repeat the operation until the particle weight increases by 10-20%, and obtain the intermediate layer particles; S4. Polyisobutylene and cyclohexane are mixed to prepare a third coating solution; the intermediate layer particles are placed in a fluidized bed, and the third coating solution is atomized and sprayed onto the surface of the intermediate layer particles until the particle weight increases by 8-10%. The particles are then dried, annealed, and matured at room temperature for 24 hours to obtain the modifier.

[0037] In some embodiments of the present invention, step S1 includes drying mesoporous silica with an average pore size of 8-12 nm at 110-120°C for 4-5 hours for later use. Butyl trifluoromethanesulfonate and dichloromethane were mixed at a mass ratio of 1:1 to obtain a mixture. The mixture was added dropwise into dried mesoporous silica while stirring. It was allowed to evaporate at room temperature for 10-12 hours, and then dried under vacuum at 40°C for 4 hours to obtain the composite.

[0038] Trifluoromethanesulfonate, being a liquid small molecule, suffers from severe phase separation and precipitation problems when directly melt-blended with polymer matrices such as polyglycolic acid (PGA) and polylactic acid (PLA). This results in uneven core layer composition, sticky particle surfaces, and hinders subsequent coating operations. This invention employs an equal-volume impregnation method, utilizing the capillary effect of mesoporous silica (8-12 nm pore size) to adsorb liquid trifluoromethanesulfonate into nanopores. After drying, a free-flowing solid composite powder is obtained, allowing the liquid ester to be uniformly mixed with the polymer matrix in powder form. This method requires no modification to existing extrusion granulation equipment and is easily scaled up for industrial applications.

[0039] Secondly, the nanopores of mesoporous silica not only serve as a physical carrier but also have a sustained-release effect. The steric hindrance effect of the pores slows down the contact rate between ester precursors and water molecules, allowing the superacid precursors to be gradually released after PGA / PLA degradation, thus prolonging the effective acidification time.

[0040] In step S2, the mass fraction of polylactic acid-glycolic acid copolymer in the first coating solution is 5-10%, the molar ratio of lactic acid to glycolic acid in the polylactic acid-glycolic acid copolymer is 85:15, the inlet air temperature is 50-60℃, and the drying time is 20-30 min.

[0041] In step S3, the air inlet temperature is 50-60℃, and the spraying temperature of the second coating liquid is 90-100℃.

[0042] In step S4, the solid content of the third coating liquid is 5-10%, the inlet air temperature is 35-40℃, and it is dried at 40℃ for 2-4 hours. Annealing treatment: 50℃ for 4 hours.

[0043] Application of a solid authigenic acid reservoir deep modification agent in deep carbonate reservoirs.

[0044] The features and performance of the present invention will be further described in detail below with reference to embodiments.

[0045] Example 1

[0046] Prepare a solid self-generating acid reservoir deep modification agent according to the following steps.

[0047] S1. Mesoporous silica with an average pore size of 8-12 nm is dried at 120°C for 5 hours and set aside. Butyl trifluoromethanesulfonate and dichloromethane are mixed at a mass ratio of 1:1 to obtain a mixture. The mixture is dripped into the dried mesoporous silica while stirring, and evaporated at room temperature for 12 hours. Then, it is vacuum dried at 40°C for 4 hours to obtain the composite. The composite is then mixed evenly with the remaining raw materials of the core layer and fed into a twin-screw extruder. The extrusion temperatures are set as follows: Zone 1 170°C, Zone 2 180°C, Zone 3 185°C, Zone 4 185°C, and die head 180°C. The screw speed is 200 rpm. Melt-blending extrusion is performed, and the extruded strips are water-cooled, stretched, and pelletized to obtain core layer particles with a diameter of approximately 0.8-1.2 mm. S2, mix polylactic acid-glycolic acid copolymer with dichloromethane to prepare a first coating solution with a mass fraction of 8%; place the core layer particles in a fluidized bed, set the inlet air temperature to 45℃ and the atomization pressure to 0.25MPa, and spray the first coating solution at the bottom. During the spraying process, maintain good fluidization of the particles and spray until the particle weight gain is 8% (based on the total mass of the modifier particles, the isolation layer accounts for 8%). Continue fluidization and drying for 30 minutes to obtain the isolation layer particles; S3, mix the raw materials of the intermediate layer evenly, place them in a melting kettle and heat to 95°C, stir until completely melted and in a transparent viscous state to prepare the second coating liquid; place the isolation layer particles in a fluidized bed, set the air inlet temperature to 50°C, and use a heated spray gun (gun head temperature 95°C) to spray the second coating liquid from the bottom, dry and solidify in the fluidized bed, repeat the spraying operation until the particle weight gain is 20% (based on the total mass of the modifier particles, the intermediate layer accounts for 20%), to obtain the intermediate layer particles; S4, polyisobutylene (number average molecular weight of 2000) is mixed with cyclohexane to prepare a third coating solution with a solid content of 8%; the intermediate layer particles are placed in a fluidized bed, the inlet air temperature is set to 38°C and the atomization pressure is 0.3MPa, and the third coating solution is atomized and sprayed onto the surface of the intermediate layer particles until the particle weight increases by 10% (the coating layer accounts for 10% of the total mass of the modifier particles). After coating, the particles are fluidized and dried at 40°C for 3 hours to remove residual cyclohexane; the dried particles are annealed in a 50°C oven for 4 hours, and then matured at room temperature for 24 hours to obtain the modifier.

[0048] In this embodiment, the core layer comprises the following raw materials by mass percentage: 50% polyglycolic acid, 30% polylactic acid, 8% trifluoromethanesulfonate, 5% ammonium fluoride, 1% hexadecyltrimethylammonium chloride, 3% mesoporous silica, and 3% plasticizer (tributyl citrate). The intermediate layer comprises, by mass percentage, the following raw materials: 70% glycolic acid and 30% hydroxypropyl methylcellulose.

[0049] Example 2

[0050] Prepare a solid self-generating acid reservoir deep modification agent according to the following steps.

[0051] S1. Mesoporous silica with an average pore size of 8-12 nm is dried at 120°C for 5 hours and set aside. Butyl trifluoromethanesulfonate and dichloromethane are mixed at a mass ratio of 1:1 to obtain a mixture. The mixture is dripped into the dried mesoporous silica while stirring, and evaporated at room temperature for 12 hours. Then, it is vacuum dried at 40°C for 4 hours to obtain the composite. The composite is then mixed evenly with the remaining raw materials of the core layer and fed into a twin-screw extruder. The extrusion temperatures are set as follows: Zone 1 170°C, Zone 2 180°C, Zone 3 185°C, Zone 4 185°C, and die head 180°C. The screw speed is 200 rpm. Melt-blending extrusion is performed, and the extruded strips are water-cooled, stretched, and pelletized to obtain core layer particles with a diameter of approximately 0.8-1.2 mm. S2, mix polylactic acid-glycolic acid copolymer with dichloromethane to prepare a first coating solution with a mass fraction of 10%; place the core layer particles in a fluidized bed, set the inlet air temperature to 45℃ and the atomization pressure to 0.25MPa, and spray the first coating solution at the bottom. During the spraying process, maintain good fluidization of the particles and spray until the particle weight gain is 5% (i.e., the isolation layer accounts for 5% of the total mass of the modifier particles). Continue fluidization and drying for 30 minutes to obtain the isolation layer particles; S3, mix the raw materials of the intermediate layer evenly, place them in a melting kettle and heat to 95°C, stir until completely melted and in a transparent viscous state to prepare the second coating liquid; place the isolation layer particles in a fluidized bed, set the air inlet temperature to 50°C, and use a heated spray gun (gun head temperature 95°C) to spray the second coating liquid from the bottom, dry and solidify in the fluidized bed, repeat the spraying operation until the particle weight increases by 15%, and obtain the intermediate layer particles; S4, polyisobutylene (number average molecular weight of 2000) is mixed with cyclohexane to prepare a third coating solution with a solid content of 10%; the intermediate layer particles are placed in a fluidized bed, the inlet air temperature is set to 38°C and the atomization pressure is 0.3MPa, and the third coating solution is atomized and sprayed onto the surface of the intermediate layer particles until the particle weight increases by 8%. After coating, the particles are fluidized and dried at 40°C for 3 hours to remove residual cyclohexane; the dried particles are annealed in a 50°C oven for 4 hours, and then matured at room temperature for 24 hours to obtain the modifier.

[0052] In this embodiment, the core layer comprises the following raw materials by mass percentage: 40% polyglycolic acid, 30% polylactic acid, 10% trifluoromethanesulfonate, 10% ammonium fluoride, 1% hexadecyltrimethylammonium chloride, 5% mesoporous silica, and 3% plasticizer (tributyl citrate). The intermediate layer comprises, by mass percentage, the following raw materials: 80% lactic acid and 20% guar gum.

[0053] Example 3

[0054] Prepare a solid self-generating acid reservoir deep modification agent according to the following steps.

[0055] S1. Mesoporous silica with an average pore size of 8-12 nm is dried at 120°C for 5 hours and set aside. Butyl trifluoromethanesulfonate and dichloromethane are mixed at a mass ratio of 1:1 to obtain a mixture. The mixture is dripped into the dried mesoporous silica while stirring, and evaporated at room temperature for 12 hours. Then, it is vacuum dried at 40°C for 4 hours to obtain the composite. The composite is then mixed evenly with the remaining raw materials of the core layer and fed into a twin-screw extruder. The extrusion temperatures are set as follows: Zone 1 170°C, Zone 2 180°C, Zone 3 185°C, Zone 4 185°C, and die head 180°C. The screw speed is 200 rpm. Melt-blending extrusion is performed, and the extruded strips are water-cooled, stretched, and pelletized to obtain core layer particles with a diameter of approximately 0.8-1.2 mm. S2, mix polylactic acid-glycolic acid copolymer with dichloromethane to prepare a first coating solution with a mass fraction of 8%; place the core layer particles in a fluidized bed, set the inlet air temperature to 45℃ and the atomization pressure to 0.25MPa, spray the first coating solution at the bottom, maintain good fluidization of the particles during the spraying process, spray until the particle weight gain is 8%, continue fluidization and drying for 30min to obtain the isolation layer particles; S3, mix the raw materials of the intermediate layer evenly, place them in a melting kettle and heat to 95°C, stir until completely melted and in a transparent viscous state to prepare the second coating liquid; place the isolation layer particles in a fluidized bed, set the air inlet temperature to 50°C, use a heated spray gun (gun head temperature 95°C) to spray the second coating liquid from the bottom, dry and solidify in the fluidized bed, repeat the spraying operation until the particle weight increases by 20%, and obtain the intermediate layer particles; S4, polyisobutylene and cyclohexane are mixed to prepare a third coating solution with a solid content of 8%; the intermediate layer particles are placed in a fluidized bed, the inlet air temperature is set to 38°C and the atomization pressure is 0.3MPa, and the third coating solution is atomized and sprayed onto the surface of the intermediate layer particles until the particle weight increases by 10%. After coating, the particles are fluidized and dried at 40°C for 3 hours to remove residual cyclohexane; the dried particles are annealed in a 50°C oven for 4 hours, and then matured at room temperature for 24 hours to obtain the modifier.

[0056] In this embodiment, the core layer comprises the following raw materials by mass percentage: 45% polyglycolic acid, 25% polylactic acid, 10% trifluoromethanesulfonate, 9% ammonium fluoride, 1% hexadecyltrimethylammonium chloride, 5% mesoporous silica, and 5% plasticizer (tributyl citrate). The intermediate layer comprises, by weight percentage, the following raw materials: 80% citric acid and 20% locust bean gum.

[0057] Example 4

[0058] Prepare a solid self-generating acid reservoir deep modification agent according to the following steps.

[0059] S1. Mesoporous silica with an average pore size of 8-12 nm is dried at 120°C for 5 hours and set aside. Butyl trifluoromethanesulfonate and dichloromethane are mixed at a mass ratio of 1:1 to obtain a mixture. The mixture is dripped into the dried mesoporous silica while stirring, and evaporated at room temperature for 12 hours. Then, it is vacuum dried at 40°C for 4 hours to obtain the composite. The composite is then mixed evenly with the remaining raw materials of the core layer and fed into a twin-screw extruder. The extrusion temperatures are set as follows: Zone 1 170°C, Zone 2 180°C, Zone 3 185°C, Zone 4 185°C, and die head 180°C. The screw speed is 200 rpm. Melt-blending extrusion is performed, and the extruded strips are water-cooled, stretched, and pelletized to obtain core layer particles with a diameter of approximately 0.8-1.2 mm. S2, mix polylactic acid-glycolic acid copolymer with dichloromethane to prepare a first coating liquid with a mass fraction of 5%; place the core layer particles in a fluidized bed, set the inlet air temperature to 45℃ and the atomization pressure to 0.25MPa, spray the first coating liquid at the bottom, maintain good fluidization of the particles during the spraying process, spray until the particle weight gain is 8%, continue fluidization and drying for 30min to obtain the isolation layer particles; S3, mix the raw materials of the intermediate layer evenly, place them in a melting kettle and heat to 95°C, stir until completely melted and in a transparent viscous state to prepare the second coating liquid; place the isolation layer particles in a fluidized bed, set the air inlet temperature to 50°C, use a heated spray gun (gun head temperature 95°C) to spray the second coating liquid from the bottom, dry and solidify in the fluidized bed, repeat the spraying operation until the particle weight increases by 20%, and obtain the intermediate layer particles; S4, polyisobutylene and cyclohexane are mixed to prepare a third coating solution with a solid content of 5%; the intermediate layer particles are placed in a fluidized bed, the inlet air temperature is set to 38°C and the atomization pressure is 0.3MPa, and the third coating solution is atomized and sprayed onto the surface of the intermediate layer particles until the particle weight increases by 10%. After coating, the particles are fluidized and dried at 40°C for 3 hours to remove residual cyclohexane; the dried particles are annealed in a 50°C oven for 4 hours, and then matured at room temperature for 24 hours to obtain the modifier.

[0060] In this embodiment, the core layer comprises the following raw materials by mass percentage: 50% polyglycolic acid, 29% polylactic acid, 10% trifluoromethanesulfonate, 10% ammonium fluoride, 1% hexadecyltrimethylammonium chloride, 5% mesoporous silica, and 5% plasticizer (tributyl citrate). The intermediate layer comprises, by mass percentage, the following raw materials: 75% chloroacetic acid and 25% hydroxypropyl methylcellulose.

[0061] Example 5

[0062] Prepare a solid self-generating acid reservoir deep modification agent according to the following steps.

[0063] S1. Mesoporous silica with an average pore size of 8-12 nm is dried at 120°C for 5 hours and set aside. Butyl trifluoromethanesulfonate and dichloromethane are mixed at a mass ratio of 1:1 to obtain a mixture. The mixture is then added dropwise to the dried mesoporous silica while stirring. The mixture is allowed to evaporate at room temperature for 12 hours, and then vacuum dried at 40°C for 4 hours to obtain a composite. The composite is then mixed evenly with the remaining raw materials of the core layer and fed into a twin-screw extruder. The extrusion temperatures are set as follows: Zone 1 170°C, Zone 2 180°C, Zone 3 185°C, Zone 4 185°C, and die head 180°C. The screw speed is 200 rpm. Melt-blending extrusion is performed, and the extruded strips are water-cooled, stretched, and pelletized to obtain core layer particles with a diameter of approximately 0.8-1.2 mm. S2, mix polylactic acid-glycolic acid copolymer with dichloromethane to prepare a first coating solution with a mass fraction of 8%; place the core layer particles in a fluidized bed, set the inlet air temperature to 45℃ and the atomization pressure to 0.25MPa, spray the first coating solution at the bottom, maintain good fluidization of the particles during the spraying process, spray until the particle weight gain is 8%, continue fluidization and drying for 30min to obtain the isolation layer particles; S3, mix the raw materials of the intermediate layer evenly, place them in a melting kettle and heat to 95°C, stir until completely melted and in a transparent viscous state to prepare the second coating liquid; place the isolation layer particles in a fluidized bed, set the air inlet temperature to 50°C, use a heated spray gun (gun head temperature 95°C) to spray the second coating liquid from the bottom, dry and solidify in the fluidized bed, repeat the spraying operation until the particle weight increases by 20%, and obtain the intermediate layer particles; S4, polyisobutylene and cyclohexane are mixed to prepare a third coating solution with a solid content of 8%; the intermediate layer particles are placed in a fluidized bed, the inlet air temperature is set to 38°C and the atomization pressure is 0.3MPa, and the third coating solution is atomized and sprayed onto the surface of the intermediate layer particles until the particle weight increases by 10%. After coating, the particles are fluidized and dried at 40°C for 3 hours to remove residual cyclohexane; the dried particles are annealed in a 50°C oven for 4 hours, and then matured at room temperature for 24 hours to obtain the modifier.

[0064] In this embodiment, the core layer comprises the following raw materials by mass percentage: 46% polyglycolic acid, 25% polylactic acid, 10% trifluoromethanesulfonate, 10% ammonium fluoride, 0.5% hexadecyltrimethylammonium chloride, 3.5% mesoporous silica, and 5% plasticizer (tributyl citrate). The intermediate layer comprises, by mass percentage, the following raw materials: 80% glycolic acid and 20% locust bean gum.

[0065] Comparative Example 1 The difference from Example 1 is that trifluoromethanesulfonate is not added to the core layer raw materials, while the other raw materials and preparation methods are the same as those in Example 1.

[0066] Comparative Example 2 The difference from Example 1 is that the isolation layer, intermediate layer and corresponding preparation steps are omitted, while the remaining raw materials and preparation steps are the same as in Example 1.

[0067] Comparative Example 3 The difference from Example 1 is that trifluoromethanesulfonate is not added to the core layer raw material, and the isolation layer, intermediate layer and corresponding preparation steps are omitted. The remaining raw materials and preparation steps are the same as those in Example 1.

[0068] Experimental Example Based on the modifying agents prepared in the above embodiments and comparative examples, the following experiments were conducted: (1) Release performance test: Weigh 10.0g of each sample and place it in 100mL of acetic acid-sodium acetate buffer solution with pH=5 (simulating the acidic environment of the reservoir). Let it stand in a constant temperature oven at 120℃. Take 5mL of supernatant every certain period of time and titrate it with 0.1mol / L NaOH standard solution to determine the total amount of acid released (calculated as HCl). Calculate the cumulative acid release rate.

[0069] (2) Dissolution performance test: Weigh 2.50g of carbonate rock powder (particle size 100-200 mesh, CaCO3 content ≥98%), place it in a beaker, add the sample amount equivalent to 15wt% HCl (for example samples, the amount is calculated based on total mass × acid source content of each layer), add deionized water to a total volume of 50mL, react at 120℃, filter, dry, weigh the undissolved rock powder, and calculate the dissolution rate. 20wt% HCl is used as a control.

[0070] (3) Corrosion rate test: Referring to the test method in patent CN111502629A, N80 steel sheets (surface area 20cm²) were subjected to corrosion rate testing. 2 The steel sheet was suspended in a test solution containing the sample (equivalent to 15 wt% HCl) and kept at 135°C for 4 hours. The weight loss of the steel sheet was measured, and the average corrosion rate was calculated.

[0071] (4) Residual rate test: Weigh 5.0g of sample, place it in 50mL of 15wt% HCl solution, let it stand at 135℃ for 24h, filter, dry, weigh the mass of undissolved residue, and calculate the residual rate.

[0072] (5) Conductivity test: Referring to the test method in patent CN111502629A, a carbonate rock slab (15cm×10cm×2cm) was used to determine the conductivity of the cracks after acid etching at 140℃ and 20MPa closure pressure.

[0073] (6) Water vapor transmission rate (WVTR) test: According to ASTM E96 standard, the sample is made into a circular disc with a diameter of 20 mm and a thickness of 3 mm, sealed in a moisture permeation cup, and the weight gain is measured at 38℃ and 90% relative humidity for 24 hours. The WVTR is then calculated.

[0074] The results are shown in the table below.

[0075] Table 1

[0076] Among them, retention rate (%, 30 days) refers to the retention rate (%) of acid release performance after 30 days of accelerated aging at 60℃ / 80%RH; retention rate (%, 60 days) refers to the retention rate (%) of acid release performance after 60 days of accelerated aging at 60℃ / 80%RH. Table 1 shows that the modifier of this invention exhibits good stability and a long shelf life under normal transportation conditions (cool and dry).

[0077] Table 2

[0078] Table 2 shows the cumulative acid release rate (%) of each sample at 120℃ and pH=5. The rapid release of the sample in the first 6 hours mainly came from the release of glycolic acid from the intermediate layer, while Comparative Example 2 (without the intermediate layer) released only 4.5% during the same period. Between 24 and 72 hours, the release curve of the sample entered a plateau phase, corresponding to the gradual hydrolysis of the core PGA / PLA framework. Between 72 and 168 hours, the release rate only increased by about 4.4%, indicating that most of the acid had been released within 72 hours.

[0079] Table 3

[0080] Table 3 shows the dissolution rate (%) of each sample on carbonate rocks at different temperatures. Example 5 showed the highest dissolution rate at all temperatures because the α-hydroxy structure of glycolic acid complexes with calcium ions, forming a soluble complex that shifts the dissolution equilibrium to the right, thus increasing the dissolution efficiency per unit amount of acid. Sophora japonica gum, as a binder, forms a gel layer by absorbing water and swelling, which delays the initial release of organic acids, allowing for a longer contact time between the acid and the rock.

[0081] Example 1: Hydroxypropyl methylcellulose is more hydrophilic than locust bean gum. The intermediate layer swells faster after absorbing water, causing some acid to diffuse with the carrier liquid before the crack wall is fully exposed, resulting in a decrease in effective utilization.

[0082] The citric acid in Example 3 has a tricarboxylic acid structure and strong complexing ability, but its molecular weight is relatively large, and it can release H+ per unit mass. +The quantity is limited, and the calcium salt of citric acid has low solubility, which will form a small amount of calcium salt deposit on the surface of the crack, hindering the continued penetration of subsequent acid.

[0083] The corrosion rate of Comparative Example 1 at 150°C / 4h was lower than that of Example 1, indicating that when the temperature is >150°C, the corrosion capacity of the weak organic acid reaches saturation, and trifluoromethanesulfonate needs to decompose to release strong acid for further corrosion.

[0084] The absence of an intermediate layer and an isolation layer in Comparative Examples 2 and 3 resulted in a decrease in the dissolution rate, indicating that the slow degradation of the single PGA / PLA framework could not release sufficient acid during the shut-in period.

[0085] Table 4

[0086] Table 4 shows the conductivity (D·cm) of acid-etched cracks for each sample under different closure pressures. The embodiments described above are some, but not all, embodiments of the present invention. The detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

Claims

1. A solid self-generating acid reservoir deep modification agent, characterized in that, It includes a core layer, an isolation layer, an intermediate layer, and a wrapper layer; The core layer comprises the following raw materials by weight percentage: Polyglycolic acid 40-50%, polylactic acid 10-30%, trifluoromethanesulfonate 5-10%, ammonium fluoride 5-10%, cetyltrimethylammonium chloride 0.5-1%, mesoporous silica 3-5%, plasticizer 3-5%; The isolation layer is a polylactic acid-glycolic acid copolymer; The intermediate layer comprises, by weight percentage, the following raw materials: 70-80% organic acid and 20-30% adhesive; The coating layer is polyisobutylene.

2. The solid self-generating acid reservoir deep modification agent according to claim 1, characterized in that, The organic acid is at least one of glycolic acid, lactic acid, citric acid, and chloroacetic acid; The adhesive is at least one of hydroxypropyl methylcellulose, polyvinylpyrrolidone, guar gum, and locust bean gum. The plasticizer is tributyl citrate or acetylated tributyl citrate.

3. The solid self-generating acid reservoir deep modification agent according to claim 1, characterized in that, The polyisobutylene has a number-average molecular weight of 1000-3000.

4. The solid self-generating acid reservoir deep modification agent according to claim 1, characterized in that, By mass fraction, the core layer is 50-70%, the isolation layer is 5-10%, the intermediate layer is 10-20%, and the covering layer is 8-10%.

5. A method for preparing a solid authigenic acid reservoir deep modification agent as described in any one of claims 1-4, characterized in that, Includes the following steps: S1, using the impregnation method, trifluoromethanesulfonate is mixed with mesoporous silica, dried to obtain a composite, and then the composite is mixed evenly with the remaining raw materials of the core layer, extruded and granulated to obtain core layer particles. S2, the polylactic acid-glycolic acid copolymer is mixed with dichloromethane to prepare the first coating solution; the core layer particles are placed in a fluidized bed, the first coating solution is sprayed from the bottom, and dried to obtain the isolation layer particles; S3, mix the raw materials of the intermediate layer evenly, heat to a molten state, and prepare the second coating liquid; place the isolation layer particles in a fluidized bed, spray the second coating liquid from the bottom, dry and solidify, repeat the operation until the particle weight increases by 10-20%, and obtain the intermediate layer particles; S4. Polyisobutylene and cyclohexane are mixed to prepare a third coating solution; the intermediate layer particles are placed in a fluidized bed, and the third coating solution is atomized and sprayed onto the surface of the intermediate layer particles until the particle weight increases by 8-10%. The particles are then dried, annealed, and matured at room temperature for 24 hours to obtain the modifier.

6. The preparation method of the solid self-generating acid reservoir deep modification agent according to claim 5, characterized in that, Step S1 includes drying mesoporous silica with an average pore size of 8-12 nm at 110-120°C for 4-5 hours for later use; Butyl trifluoromethanesulfonate and dichloromethane were mixed at a mass ratio of 1:1 to obtain a mixture. The mixture was added dropwise into dried mesoporous silica while stirring. It was allowed to evaporate at room temperature for 10-12 hours, and then dried under vacuum at 40°C for 4 hours to obtain the composite.

7. The preparation method of the solid self-generating acid reservoir deep modification agent according to claim 5, characterized in that, In step S2, the mass fraction of polylactic acid-glycolic acid copolymer in the first coating solution is 5-10%, the molar ratio of lactic acid to glycolic acid in the polylactic acid-glycolic acid copolymer is 85:15, the inlet air temperature is 50-60℃, and the drying time is 20-30 min.

8. The preparation method of the solid self-generating acid reservoir deep modification agent according to claim 5, characterized in that, In step S3, the air inlet temperature is 50-60℃, and the spraying temperature of the second coating liquid is 90-100℃.

9. The preparation method of the solid self-generating acid reservoir deep modification agent according to claim 5, characterized in that, In step S4, the solid content of the third coating liquid is 5-10%, the inlet air temperature is 35-40℃, and it is dried at 40℃ for 2-4 hours. Annealing treatment: 50℃ for 4 hours.

10. Application of a solid authigenic acid reservoir deep modification agent in deep carbonate reservoirs.

Citation Information

Patent Citations

  • Solid acid for acid fracturing capacity increasing revamping

    CN102676150A

  • Efficient retarding solid acid system harmless to reservoir

    CN111154477A

  • Solid acid precursor for reservoir transformation

    CN116875296A

  • Controllable release type organic solid acid preparation method

    CN119552647A